2012
DOI: 10.22401/jnus.15.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Spectrophotometric Methods for the Determination of Chloramphenicol in Pharmaceutical Preparations

Abstract: Simple and sensitive kinetic methods are described for the determination of chloramphenicol in pure form and pharmaceutical preparations. The methods are based on oxidativecoupling reaction between reduced chloramphenicol (by zinc powder and concentrated hydrochloric acid) with promethazine hydrochloride in the presence of sodium periodate yielding a highly colored product at room temperature, the reaction is followed spectrophotometriclly at λ max = 590 nm. Initial rate and fixed time (at 20 minutes) methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results of the proposed method for three type of samples in this study were compared statistically with reported method that used metacresol purple (MCP) as a chromogenic reagent and spectrophotometric determination of SC (32) . The results are summarized from Table 11.…”
Section: * Average Of Five Determinationsmentioning
confidence: 99%
“…The results of the proposed method for three type of samples in this study were compared statistically with reported method that used metacresol purple (MCP) as a chromogenic reagent and spectrophotometric determination of SC (32) . The results are summarized from Table 11.…”
Section: * Average Of Five Determinationsmentioning
confidence: 99%
“…For the determination of studied drug, various methods have been reported in literature; these methods included: High performance liquid chromatography (HPLC) which is one of the most powerful and versatile tool for the quantitative determination of CAP (Hoang et al, 2015;Suguna et al, 2014;Mallu et al, 2011), also LC-MS (Bjorn, 2013), LC-MS-MS (Rocha et al, 2015). Other analytical methods have been reviewed in literature these methods included: voltammetry (Yafeng et al, 2014), Polarography (Suliman and Razzak, 2000), so that various spectrophotometric methods have been used (Alshirifi and Alhameedi, 2016;Suguna et al, 2016;Wafi et al, 2015;Al-Abachi et al, 2014;Al-Sabha and Al-Hammoshi, 2013;Sinan and Al-Abachi, 2010;Sayhood et al, 2013;Al-Sabha and Rasheed, 2010;Al-Ward, 2012).…”
Section: Cap Structure Mwt = 3231322 G / Molmentioning
confidence: 99%
“…Furthermore, BH-HCl is one of the mucous-modifying drugs that aid expectoration by improving the flow characteristics of bronchial mucous [3,4]. A literature review indicated the determination of bromhexine hydrochloride in dosage form, either in combined form or alone, by spectrophotometric [5][6][7][8][9][10][11], potentiometric [12], voltammetric [13], colorimetric [14], chemiluminescence [15,16], TLC [17], HPLC [18][19][20][21][22][23][24][25], RRLC-MS/MS [26], and HPTLC-HPLC [27]. This study presents a new method to determine BH-HCl in pharmaceutical formulations using tetraphenylborate as a precipitating reagent to form a yellowish-white precipitate with the use of a homemade instrument.…”
Section: Introductionmentioning
confidence: 99%